Pengaruh Teknik Relaksasi Otot Progresif Terhadap Kualitas Tidur Mahasiswa - Indrawan Manitu; Noldin Sirumpa (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2022)
Introduction: Sleep is one of the physiological needs of humans that function for the recovery process of the body. College students are one of the populations with a high prevalence of sleep problems. Aims: knowing the influence of progressive muscle relaxation techniques on students' sleep quality. Method: This research is a type of quasi-experiment with pretest and posttest with a control group design. The sampling technique is stratified proportional random sampling involving 64 respondents divided into 2 groups: the intervention group (conducting progressive muscle relaxation for 4 days) and the control group (performing standard intervention: listening to musical instruments) with 32 respondents each. Sleep quality is measured by the Pittsburgh Sleep Quality Index (PSQI). The significance level in the study was 95% (p<0.05). Results: Showed significant differences in sleep quality before and after progressive muscle relaxation (p= 0.000). Showed no significant difference between the sleep quality of the intervention group and the control group after the post-test (p= 0.048). Conclusion: That there is an influence of progressive muscle relaxation techniques on the sleep quality of students. Progressive muscle relaxation can activate the parasympathetic nerve to stimulate the hypothalamus to produce serotonin which can cause sleep